2010
DOI: 10.1371/journal.ppat.1001148
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania-Induced Inactivation of the Macrophage Transcription Factor AP-1 Is Mediated by the Parasite Metalloprotease GP63

Abstract: Leishmania parasites have evolved sophisticated mechanisms to subvert macrophage immune responses by altering the host cell signal transduction machinery, including inhibition of JAK/STAT signalling and other transcription factors such as AP-1, CREB and NF-κB. AP-1 regulates pro-inflammatory cytokines, chemokines and nitric oxide production. Herein we show that upon Leishmania infection, AP-1 activity within host cells is abolished and correlates with lower expression of 5 of the 7 AP-1 subunits. Of interest, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(140 citation statements)
references
References 51 publications
2
132
1
2
Order By: Relevance
“…Activation of c-Fos and c-Jun to drive MDR1 overproduction in Sb R LD-infected Mϕs seems unique. Indeed, it has been reported previously that in different species of Leishmania, including LD, surface metalloprotease gp63 inactivates all the subunits of the AP-1 transcription factor, because all the subunits, such as c-Fos, c-Jun, Jun B, Jun D, and Fra 1, have putative sites of gp63 cleavage (32). The contrast, compared with our findings, could be explained by experimental differences between the two studies.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Activation of c-Fos and c-Jun to drive MDR1 overproduction in Sb R LD-infected Mϕs seems unique. Indeed, it has been reported previously that in different species of Leishmania, including LD, surface metalloprotease gp63 inactivates all the subunits of the AP-1 transcription factor, because all the subunits, such as c-Fos, c-Jun, Jun B, Jun D, and Fra 1, have putative sites of gp63 cleavage (32). The contrast, compared with our findings, could be explained by experimental differences between the two studies.…”
Section: Discussioncontrasting
confidence: 86%
“…Previous reports suggested that activation of ERK is the key step for IL-10 induction (31). Interestingly, infection with Sb S LD results in the inactivation of host ERK, NF-κB, and JNK, thereby favoring establishment of the parasite (32). In our study, we also did not observe any activation of ERK or NF-κB in Mϕs infected with Sb S LD, although Sb R LD activates ERK and nuclear translocation of NF-κB involving p50/c-Rel, leading to IL-10 induction, through interaction with IL-10 promoter site II (−583/ −593).…”
Section: Discussionmentioning
confidence: 99%
“…SHP-1 reversibly associates with the IFN-␣ receptor complex upon IFN stimulation and selectively inhibits the JAK/STAT signaling pathway (3). SHP-1 is also known to have an inhibitory effect on JAK2, the Erk1/Erk2 MAPK, NF-B, IRF-1, and AP-1, which in turn inhibit IFN-␥-inducible macrophage function (5,52). The pattern of abundance of SHP-1 was observed in two of the replicate experiments and was identified based on a single peptide in the proteomic screen.…”
Section: Resultsmentioning
confidence: 94%
“…A decrease in Wnt5a protein upon L. donovani promastigote infection could be due to the activity of L. donovani proteases, such as GP63. This concept arises from the observed inhibition of the diminution of Wnt5a levels of infected cells through administration of phenanthroline, an inhibitor of GP63-like protease activity (31) (Fig. 1E).…”
Section: Donovani Infection Leads To Disruption Of the Steady-statmentioning
confidence: 99%